Fabrication of Monolithic Dye-Sensitized Solar Cell Using Ionic Liquid Electrolyte - Seigo Ito; Kaoru Takahashi (International Journal of Photoenergy)
To improve the durability of dye-sensitized solar cells (DSCs), monolithic DSCs with ionic liquid electrolyte were studied. Deposited by screen printing, a carbon layer was successfully fabricated that did not crack or peel when annealing was employed beforehand. Optimized electrodes exhibited photovoltaic characteristics of 0.608 V open-circuit voltage, 6.90 cm−2 mA short-circuit current, and 0.491 fill factor, yielding 2.06% power conversion efficiency. The monolithic DSC using ionic liquid electrolyte was thermally durable and operated stably for 1000 h at 80°C.